Underactuated robotic hand for a fully automatic dishwasher based on grasp stability analysis*. (16th February 2022) - Kinugawa, Jun; Suzuki, Hiroki; Terayama, Junya; Kosuge, Kazuhiro
Abstract : In this study, we propose a fully automatic dishwashing and arranging system. The user simply places the used dishes on the worktop, and the system automatically arranges them in the dish basket and cleans the dishes in the dishwasher. The washed dishes are automatically arranged on the worktop by the system. This eliminates the need to manually load and unload dishes. To realize this system, we develop a novel underactuated robotic hand for grasping multiple shaped dishes stably. The motion of the underactuated mechanism used in the robotic hand for the dishes is modeled, and stability is analyzed. The dimensions of the link used for the underactuated mechanism are determined based on the results. In addition, we conduct grasp experiments for dishes of various shapes, and an experiment on arranging dishes to confirm the effectiveness of the proposed system. The proposed hand is expected to contribute to the full automation of the dishwashing process in restaurants and other commercial kitchens as well as in the standard home. GRAPHICAL ABSTRACT: UF0001